2018
DOI: 10.1021/acs.macromol.8b00049
|View full text |Cite
|
Sign up to set email alerts
|

Decoration of Polyfluorene-Wrapped Carbon Nanotubes via Strain-Promoted Azide–Alkyne Cycloaddition

Abstract: Developing methodologies that can efficiently decorate carbon nanotube surfaces with various molecular structures while avoiding damage to nanotube optoelectronic properties is an ongoing challenge. Here, we outline a methodology to perform chemistry on the nanotube surface without perturbing optoelectronic properties. Reactive, noncovalently functionalized polymer–nanotube complexes were prepared using polyfluorene with azide groups in its side chains. The azides enable strain-promoted azide–alkyne cycloaddit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 84 publications
1
30
0
Order By: Relevance
“…To prepare reactive polymer–SWNT complexes, we first synthesized an aryl iodide‐containing polyfluorene ( PF‐PhI ). The precursor polyfluorene with alkyl bromides in the side chain ( PF‐Br ) was prepared according to literature procedures . Gel permeation chromatography analysis showed that PF‐Br had an M n of 100 kDa, corresponding to a degree of polymerization of ~101, and a dispersity (Đ) of 3.9.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To prepare reactive polymer–SWNT complexes, we first synthesized an aryl iodide‐containing polyfluorene ( PF‐PhI ). The precursor polyfluorene with alkyl bromides in the side chain ( PF‐Br ) was prepared according to literature procedures . Gel permeation chromatography analysis showed that PF‐Br had an M n of 100 kDa, corresponding to a degree of polymerization of ~101, and a dispersity (Đ) of 3.9.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently been investigating a simple way to simultaneously decorate single‐walled carbon nanotubes (SWNTs) while avoiding SWNT damage . Since their discovery in 1991, efforts have been made to exploit the extraordinary mechanical, structural, and optoelectronic properties of SWNTs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has been investigating the decoration of single‐walled carbon nanotubes (SWNTs) with conjugated polymers to impart reactivity to the polymer–nanotube complex . This strategy operates by incorporating functional groups into the conjugated polymer side chains to perform chemistry on the adsorbed conjugated polymer, which avoids damage to the SWNT structure.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy operates by incorporating functional groups into the conjugated polymer side chains to perform chemistry on the adsorbed conjugated polymer, which avoids damage to the SWNT structure. By incorporating azide groups into the conjugated polymer side chains, copper‐catalyzed or strain‐promoted azide–alkyne cycloaddition (CuAAC) can be used to decorate the SWNT surface. We have also incorporated aromatic iodides to enable Pd cross‐coupling to the polymer–SWNT conjugate, and have prepared water‐dispersible polymer–SWNT complexes for aqueous click functionalization .…”
Section: Introductionmentioning
confidence: 99%